Oral problems and associated risk indicators in adults in the Russian Federation, India, and China - Rahul Bawankule; Abhishek Singh; Kaushalendra Kumar; Sarang Pedgaonkar (BMC, 2019)
Abstract Background Oral problems, known as a neglected epidemic, have become prevalent in Brazil, the Russian Federation, India, China, and South Africa (BRICS) countries in last decade. The objective of the study is to examine the prevalence and associated risk indicators of oral problems in adults in the Russian Federation, India, and China in BRICS countries. Methods We used data from the first round of the Study of Global AGEing and Adult Health (SAGE), conducted by WHO in 2007-10 in selected BRICS countries. Oral problems are defined as if an adult had any mouth and/or teeth related problems including swallowing problems in last 1 year of the survey. We estimated the mean age of adults who had oral problems and used a t-test for comparing it by sex of adults. We determined the prevalence of oral problems in adults. We designed a hierarchical conceptual model to identify associated risk indicators with oral problems. Finally, we applied a multivariable binary logistic regression model based on a conceptual model to examine associated socioeconomic and demographic, behavioral and nutritional risk indicators and systemic diseases - diabetes, hypertension, and angina pectoris/angina with oral problems in adults. Results The mean age of adults who had oral problems is lowest in India (57 years; SD: 15) and highest in China (65 years; SD: 11). However, it does not vary by sex of adults except India. The prevalence of oral problems is highest in the Russian Federation (35%) and lowest in China (9%). Adults with body mass index (BMI) less than 25 kg/m2, age 45 years or more, diabetes, hypertension, and angina pectoris/angina have a higher risk of oral problems. Females and adults using alcohol are also more likely to have oral problems in selected countries. Conclusions The study concludes that females, adults using alcohol and those having any systemic disease are at higher risk of oral problems in the Russian Federation, India, and China. A one-third of adults had oral problems in particularly, in the Russian Federation; thus there is an urgent need to formulate oral policy and program, which the country currently lacks in.